EATING WASPS - ANITA NAIR (CHENNAI CINTEXT, 2018)
In a small town by the river Nila, a thirty-five year old writer kills herself. No one knows why.Fifty-two years later, an antique cupboard in a private resort opens to reveal a frightened child. And the mystery begins to unravel.
Keywords: ENGLISH NOVEL; INDIAN ENGLISH NOVEL